Challenges of practicing digital imaginaires in collaborative museum design. Issue 3 (2nd July 2020) - Olesen, Anne Rørbæk; Holdgaard, Nanna; Laursen, Ditte
ABSTRACT: The main objective of this article is to reflect upon the integration of digital media in museums by analysing how the digital is imagined and practised in co-design processes at three Danish art museums. With conceptual reference to Flichy's 'imaginaire', we analyse project descriptions written by project participants to obtain funding. The project descriptions represent initial collective visions and reveal imaginations about the capabilities of digital technology. We find that two categories of imaginaires are similar across the cases and we analyse ethnographic data to identify challenges of practicing these. Our findings suggest that challenges mostly emerge in co-design activities or when such activities are not prioritised. The article concludes with reflections on the integration of digital media in museums and the paradoxical nature of the collective project vision as both a necessary driver and constrainer of collaborative museum design.